Flow cytometric assessment of canine erythrocytes and platelets for dog erythrocyte antigen 1.1 - Lucidi, Cynthia de A. [UNESP]; Takahira, Regina Kiomi [UNESP]; Gerlach, John A.; Davis, John M.; Schwartz, Kenneth A.; Scott, Michael A. (Wiley-Blackwell, 2011)
Background: In human medicine, transfusion of ABO-mismatched platelets has been associated with shortened platelet survival and refractoriness to platelet transfusion because of expression of certain blood group antigens on platelets. It remains unknown if canine platelets express dog erythrocyte antigens (DEAs). Objective: The aim of this study was to develop a flow cytometric assay for DEA 1.1 and determine whether DEA 1.1 is present on canine platelets.Methods: Blood was collected from 172 clinically healthy dogs. Platelets and erythrocytes from each dog were tested for DEA 1.1 by flow cytometry using anti-DEA 1.1 blood-typing sera. Erythrocytes from each dog were also assessed for DEA 1.1 using a standard tube-typing test (T1) and using a second tube method (T2), if the flow cytometric and T1 results differed.Results: Using flow cytometry, DEA 1.1 was detected on erythrocytes of all 110 dogs shown by T1 or T2 testing to be DEA 1.1-positive. Initial results of the T1 test had a diagnostic accuracy of 93% (160 correct/ 172 tests). The frequency of erythrocyte DEA 1.1 positivity in previously untyped dogs (n = 118) was 56%. DEA 1.1 expression was not detected on platelets from DEA 1.1-positive dogs.Conclusions: Flow cytometry was a reliable method for detection of DEA 1.1 on canine erythrocytes. The absence of DEA 1.1 on platelets from DEA 1.1-positive dogs suggests that their platelets do not express DEA 1.1 and will not induce production of anti-DEA 1.1 antibodies that might lead to platelet refractoriness or reactions to a subsequent transfusion of DEA 1.1positive erythrocytes.
Keywords: Blood compatibility; blood-typing; immunohematology; platelet antigens; transfusion reaction